Exploring EFL students’ motivational factors in an academic writing classroom - Adventi, Arinda Luthyara; Mali, Yustinus Calvin Gai; Listyani (Journal of English and Education (JEE), 2025)
Academic writing is a fundamental competency that should be mastered by English as a Foreign Language (EFL) students. However, to do so is often a challenging task for the students. That challenge might affect students’ writing motivation. This study aims to explore possible factors that motivate EFL students’ motivation in an academic writing class. To achieve that goal, the researchers first conducted a literature review of 15 relevant articles published in national and international journals. Then, the researchers conducted a semi-structured interview with four students to discuss the results of the literature review analysis. With a rigorous peer debriefing data analysis strategy, the research findings presented four main themes as the answers to the research question. The themes were related to technology and visual aids, learning goals, students' relationships and social environment, and lecturers' excellent competency. The findings were then discussed in light of the relevant literature. Practical recommendations (i.e., providing various writing template, spending enough time for writing consultation, and encouraging students to stay motivated in the writing class) for EFL lecturers teaching the academic writing class and ideas for future research, which included expanding the research participants and contexts to confirm or challenge the motivational factors revealed in the current study, were presented.